Sosialisasi Tentang Tahapan Pelaksanaan Pengadaan Tanah untuk Kepentingan Umum: Studi Kasus di Kecamatan Sepaku Pada Proyek Penanganan Banjir Sungai Sepaku,Ibu Kota Nusantara - Jusuf Leiwakabessy; Yoseph Alberthus Lamere; Van Basten Simamora (Karawo : Journal of Community Service (KJCS), 2023)
In the Development of the Archipelago Capital in Sepaku District, North Penajam Paser Regency, East Kalimantan. One of them is in the Sepaku River Flood Management Development Project, Sepaku District, which in the development process still has obstacles. The obstacle faced is because the land is included in a residential area. To provide land for the construction of the embankment, it is necessary to procure it. Policies in land acquisition for development in the public interest are regulated in the 1945 Constitution, Law Number 5 of 1960concerningBasic Regulations on Agrarian Principles (UUPA) and Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest. The research method in writing this journal is the empris juridical approach method. In summary, the conclusion of the discussion is about the stages of implementing land acquisition for the public interest in the Sepaku river flood management project.